(untitled) (Journal of Pathology of Nepal, 2016)
Intraosseous lipoma is an uncommon benign bone neoplasm with most of them detected incidentally on multimodality imaging while being evaluated for an unrelated pathology. Long and cancellous bones are commonly involved. This lesion can present a diagnostic challenge to those uninitiated in its appearence because they can be often mistaken for other benign or malignant bone lesions such as enchondroma, fibrous dysplasia, osteoblastoma, bone infarct, bone cyst and chondrosarcoma. Here we report a case of symptomatic calcaneal lipoma in a 50 year old lady who presented with heel pain. Plain X-ray suggested cystic lesion of calcaneum. MRI revealed the presence of intralesional fat and histopathological examination confirmed the diagnosis. We present this report for its rarity and the clinching MRI features of this lesion, the excellent prognosis and near negligible recurrence rates, so that misdiagnosis leading to unnecessary workup, biopsy and treatment may be avoided, especially in asymptomatic patients.